(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic and state determinations of social isolation as a way to contain the disease negatively impacted the mental health, learning and development of children. In this way, after the pandemic period, it was possible to identify an increase in children referred to the Expanded Family Health Center (EFHC) of a Primary Health Care Center in Brasília-DF due to delays in neuropsychomotor development. Taking into account the high demand and the potential of early intervention to obtain positive effects on child development, the organization of a group was identified as a powerful strategy for coping with the presented problem. The main objective of this article is to report the experience of planning and executing an intervention strategy developed in Primary Health Care with the intention of improving the problems identified in daily professional life. of the study design process. From the application of the intervention project, it is concluded that the proposed objectives were achieved, obtaining successful experiences in the scenario where the problems were identified.